Sharpening the Industrial Engineering and Management Qualification Profile: Research Findings from Austria - Zunk, Bernd Markus; Sadei, Christoph (International Journal of Industrial Engineering and Management, 2015)
Since the introduction of Industrial Engineering and Management (IEM) degree programs at Austrian Higher Education Institutions (HEIs) in the 1950’s, the number of IEM degree programs has been rising continuously. Accelerated by changes in the educational system on the European Union level started in 1990, problems regarding the comparability of IEM qualification profiles have increased. Tosharpen the IEM qualification profile, this paper presents (i) a recommendation of an IEM qualification profile approved by alumni associations of German-speaking countries, (ii) a structure to compare IEM degree programs and (iii) results from two online surveys among IEM professionals and IEM students, as well as human resource managers. Article history: Received (25.05.2015); Revised (01.09.2015); Accepted (11.09.2015)